Pengaruh Green Ability, Green Motivation, Green Opportunity terhadap Organizational Performance Dengan Green Innovation Sebagai Variabel Intervening Pada Industri Percetakan dan Reproduksi Media Rekaman - Muhammad Rafi; Gia Rizky (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aimed to analyze the influence of green ability, green motivation, and green opportunity on organizational performance through green innovation in the printing and reproduction industry of recorded media in Indonesia. The sampling technique in this study used the simple random sampling method with total of 114 employees as respondents. Primary data in this study were collected using questionnaire distributed via Google Form, which had been tested for validity and reliability. Data analysis in this study used outer model test consisting of convergent validity test and reliability test, and inner model test consisting of an R Square test and hypothesis test using SmartPLS version 4.0.9.9. The results showed that green ability, green motivation, green opportunity had positive and significant effect on organizational performance, green ability, green motivation, green opportunity had positive and significant effect on green innovation, green innovation had positive and significant effect on organizational performance, and green innovation had partial mediating effect on the relationship between green ability, green motivation, green opportunity and organizational performance. Further research could deepen the analysis of other factors that influenced organizational performance.